2020
DOI: 10.1021/acsami.9b21466
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Graded Silicon Nanowire Arrays via Chemical Etching: Engineering Optical Properties at the Nanoscale and Macroscale

Abstract: We report on a quick, simple, and cost-effective solution-phase approach to prepare centimeter-sized morphology-graded vertically aligned Si nanowire arrays. Gradients in the nanowire diameter and shape are encoded through the macroscale substrate via a "dip-etching" approach, where the substrate is removed from a KOH etching solution at a constant rate, while morphological control at the nanowire level is achieved via sequential metalassisted chemical etching and KOH etching steps. This combined approach prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(96 citation statements)
references
References 55 publications
0
83
0
Order By: Relevance
“…Furthermore, Wendisch et al recently reported a solution-phase shaping method by the combination of MACE and KOH etching for producing the morphology-graded vertical Si nanowires [ 74 ]. MACE and KOH etching steps were sequentially conducted to yield bi-segmented Si nanowires with controlled lengths and diameters ( Figure 3 f), which provides another way to maximize absorbability of vertical Si nanowire arrays in specific wavelengths of light.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Wendisch et al recently reported a solution-phase shaping method by the combination of MACE and KOH etching for producing the morphology-graded vertical Si nanowires [ 74 ]. MACE and KOH etching steps were sequentially conducted to yield bi-segmented Si nanowires with controlled lengths and diameters ( Figure 3 f), which provides another way to maximize absorbability of vertical Si nanowire arrays in specific wavelengths of light.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…( a ) reprinted by permission from Springer Nature: Springer Scientific Reports [ 61 ], Copyright 2019; ( b ) reprinted with permission from [ 21 ]. Copyright 2012 American Chemical Society; ( c , d ) reprinted from [ 70 ], with the permission of AIP Publishing; ( e ) reprinted by permission from Springer Nature: Springer Nature Nanotechnology [ 73 ], Copyright 2008; ( f ) reprinted with permission from [ 74 ]. Copyright 2020 American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…The most used one remains the gold due to the best quality of fabricated Si NWs, for the stability in the etching solution compared to the silver, and for the fast and high tunable etching rate compared to other metals. Ti and other material such as AZO were also used as an adhesion layer for thick Au films, permitting to improve the film stability [ 126 , 127 , 138 ]. Kim et al report the application of an Au/Ag bilayer mesh to avoid the issue on the Ag stability and anodic dissolution during the etching [ 113 ].…”
Section: Metal Film or Two Step Macementioning
confidence: 99%
“…Other than the design of narrow gap between metal nanostructures, the manipulation of incident light by three-dimensional nanostructures has also been considered as a potential strategy [ 24 ]. For example, hexagonal-packed silver-coated silicon nanowire arrays could be made as a nanogap-free SERS system with long-range electric fields [ 25 ].…”
Section: Introductionmentioning
confidence: 99%